The safety and efficacy of steroid treatment for acute spinal cord injury: A Systematic Review and meta-analysis. Issue 2 (February 2020) - Sultan, Ihtisham; Lamba, Nayan; Liew, Aaron; Doung, Phoung; Tewarie, Ishaan; Amamoo, James J.; Gannu, Laxmi; Chawla, Shreya; Doucette, Joanne; Cerecedo-Lopez, Christian D.; Papatheodorou, Stefania; Tafel, Ian; et al.
Abstract: Introduction: The role for steroids in acute spinal cord injury (ASCI) remains unclear; while some studies have demonstrated the risks of steroids outweigh the benefits, a meta-analyses conducted on heterogeneous patient populations have shown significant motor improvement at short-term but not at long-term follow-up. Given the heterogeneity of the patient population in previous meta-analyses and the publication of a recent trial not included in these meta-analyses, we sought to re-assess and update the safety and short-term and long-term efficacy of steroid treatment following ASCI in a more homogeneous patient population. Materials and methods: A literature search was conducted on PubMed, EMBASE and Cochrane Library through June 2019 for studies evaluating the utility of steroids within the first 8 h following ASCI. Neurological and safety outcomes were extracted for patients treated and not treated with steroids. Pooled effect estimates were calculated using the random-effects model. Results: Twelve studies, including five randomized controlled trials (RCTs) and seven observational studies (OBSs), were meta-analyzed. Overall, methylprednisolone was not associated with significant short-term or long-term improvements in motor or neurological scores based on RCTs or OBSs. An increased risk of hyperglycemia was shown in both RCTs (RR: 13.7; 95% CI: 1.93, 97.4; 1 study) and OBSs (RR: 2.9; 95% CI: 1.55, 5.41; 1 study). Risk for pneumonia was increased with steroids; while this increase was not statistically significant in the RCTs (pooled RR: 1.16; 95% C.I: 0.59, 2.29; 3 studies), it reached statistical significance in the OBSs (pooled RR: 2.00; 95% C.I: 1.32, 3.02; 6 studies). There was no statistically significant increased risk of gastrointestinal bleeding, decubitus ulcers, surgical site infections, sepsis, atelectasis, venous thromboembolism, urinary tract infections, or mortality among steroid-treated ASCI patients compared to untreated controls in either RCTs or OBSs. Conclusions: Methylprednisolone therapy within the first 8 h following ASCI failed to show a statistically significant short-term or long-term improvement in patients' overall motor or neurological scores compared to controls who were not administered steroids. For the same comparison, there was an increased risk of pneumonia and hyperglycemia compared to controls. Routine use of methylprednisone following ASCI should be carefully considered in the context of these results. Abstract : Neuroscience; Neurology; Neurosurgery; Trauma; Intensive care medicine; Endocrine system; Steroids; Methylprednisolone; Adverse effects; Acute spinal cord injury; Spinal cord injury; Pneumonia; Hyperglycemia.